PERAN ORANG TUA TERHADAP PEMBENTUKAN KARAKTER PESERTA DIDIK DI MI MUHAMMADIYAH PANGKALAN BERANDAN - Anta Jaya (Journal of Community Devation, 2025)
This research aims to examine the role of parents in forming the character of students at MI Muhammadiyah Pangkalan Berandan, describe the character of students at MI Muhammadiyah Pangkalan Berandan, measure the influence of the role of parents on the formation of students' character at MI Muhammadiyah Pangkalan Berandan. This research is a type of quantitative research with the subjects being students at MI Muhammadiyah Pangkalan Berandan, as well as with the subjects being students in grades V and VI at MI Muhammadiyah Pangkalan Berandan. Data collection tools include questionnaires, observations and interviews. The data analysis techniques used in this research are descriptive analysis and correlation analysis. The main findings of the research show that the results of the correlation product moment calculation show that rcount is 0.938 and rtable = 0.514 at a significance level of 5%, meaning rcount > rtable, so there is a significant influence on the role of parents on the formation of students' character at MI Muhammadiyah Pangkalan Berandan, with the test It is known that the role of parents contributes 88% in influencing the character of students.